Buklet Digital sebagai Pengingat Warga terhadap Protokol Kesehatan Covid-19 - Prima Agustina Mariamurti; Tania Intan; Sri Rijati Wardiani (Jurnal Pemberdayaan Masyarakat, 2021)
People were stunned as the number of Covid-19 victims around the world exploded. Everyone should live with this virus that has not yet found a cure and the number of infected and dead patients is increasing. Every government put health protocols to protect the citizen's well-being. The 3M's behaviour (wearing a mask, maintaining distance, washing hands) will prevent people from being infected with the virus. However, the number of mortality has not decreased. Through community service activities that are integrated with student community service programs, online interviews and surveys are conducted with partners around student residences to find out public awareness of health protocols. People already know and implement this protocol, but the pandemic condition which has been going on for almost a year has made them ignorant and negligent. This situation requires a constant reminder about the Covid-19 virus and its prevention. One option that can be accessed online is through digital booklets, which can be easily opened from any gadget and also be distributed to others. This activity also shows that to get through the pandemic period, everyone must have insight and a willingness to receive relevant knowledge.